PRACTICALITIES OF AGENT BANKING FOR FINANCIAL INCLUSION IN RURAL AREAS OF BANGLADESH - Kabir, Mohammad Rezaul; Fatema, Kaniz; Das, Ashok Bijoy; Barman, Nityananda Chandra (Indian Journal of Finance and Banking, 2024)
Agent banking is an indispensable part of the inclusive banking system for advancing greater financial inclusion in Bangladesh. These services represent the new extension of branch banking, offering formal banking services in rural regions at a low cost via agents and outlets. The purpose of this study is to examine the agent banking practical uses to meet the financial services needs of the rural population in Bangladesh. Moreover, this study investigates the relation between agent banking presence in rural areas and its uses. Five years of secondary data regarding agent banking have been collected from the statistics department of Bangladesh Bank and presented in tabular form. Besides, to portrait the real picture of practical uses of agent banking, a rural user’s case study has been used in this study. Descriptive with an analytical approach has also been used to analyze the data. Besides, correlation analysis has also been used to measure the relation between agents, outlets, and rural practices. This study found that agent banking services are practically used in rural areas for deposit collection, loan disbursements, remittance services, and utility bill payment. Moreover, it has discovered a favorable relationship between agent banking presence and useful applications in rural areas. The practical applications of the agent banking have advanced significantly in rural areas and included those who were previously denied access to these financial services. While the number of agents and outlets are not sufficient, total rural account holders in agent banking remain low compared to the rural adult population. JEL Classification Codes: G21, G51, G53, C87.